Empirical examination of societal, financial and technology-related challenges amid COVID-19 in service supply chains: evidence from emerging market - Ajmal, M.M. (Emerald Group Holdings Ltd., 2021)
Purpose: This paper reports an empirical examination of the societal, financial and technology-related challenges amid the ongoing pandemic (COVID-19) in the service supply chain network. Design/methodology/approach: A combination of qualitative approach (for items generation pertinent to the constructs involved) and quantitative approach (self-administered questionnaires from the top and middle management of the sampled companies) was used for data collection. In total, 272 complete responses were received and analyzed through structural equation modeling. Findings: The results provided empirical evidence that social and physical distancing, travel restrictions, work from home and lockdown practices have two conflicting effects: On one hand, these practices have contributed to the reduction of economic activities, including the low economic outlook, low productivity, high unemployment, poverty, fall in customer demands, dissatisfaction and mental health, that ultimately impacts rise financial and societal issues. On the other hand, the results revealed an insignificant influence of COVID-19 on creating technology-related challenges in the service sector. It shows that the organizations are doing well in combating the technology-related challenges amidst the current pandemic. Research limitations/implications: Findings of the inquiry recommend implications for the services industry to harmonize a comprehensive strategy and revisit the global norms in sustainable supply chain management activities that have been the backdrop in their operations for a long time. Practical implications: Findings of the inquiry recommend implications for the services industry to harmonize a comprehensive strategy and revisit the global norms in supply chain management activities that have been the backdrop in their operations for a long time. Originality/value: Prior studies in the context of the COVID-19 outbreak and its implications have given more attention to the exploratory and theoretical discussion than to empirical evidence. This paper contributes to filling this knowledge gap by empirically exploring the societal, financial and technology-related challenges created by COVID-19. The analysis in this paper covers three dimensions of the PEST model, namely economic, societal and technological factors. This study also helps in laying out a platform for investigating the PEST (political, economic, social and technological) model for guiding the services industry in strategic decision-making in a new era due to COVID-19. Â© 2021, Emerald Publishing Limited.